The Role of K-cycle on unified equation of state - YAHYA, Mochammad Utoro (Universitas Gadjah Mada, 2000)
In this research, the unified equation of state for gaseozcs, liquid and solid systems was obtained thoroughly. The unified equation of state for any system was derived and verified thoroughly through the study of thermodynamic laws, especially first and second laws, mathematical operation called variable sepration method and supported by the application of K-cycle. K-cycle was a thermodynamics cycle at isothermal reversible condition consisted of two isomolar and two isobar processes. The system of real gas solution as well as binary liquid solution followed the unified equation in the (U form of ( P + d z ) ) ( r - E ) = C R T ; where is internal pressure, P is